Nutrient timing fueling strategies to unlock peak performance - Link, Lauren (Champaign, IL Human Kinetics, 2025)
"As an athlete, you're likely bombarded by advice from coaches, trainers at the gym, and teammates and friends about what you should be eating, how much, and when. You probably even get advice from people on social media who have never even met you! Whether you're an endurance runner, a team sport competitor, or a strength and power athlete, Nutrient Timing: Fueling Strategies to Unlock Peak Performance gives you science-backed advice that has been translated into practical recommendations to help optimize your training, boost performance, and accelerate recovery. Learn why nutrient timing matters and how to identify your specific timing needs. Find carb, protein, fat, fluid, and supplement recommendations-for before, during, and after training or competition-that are specific to your situation, activity level, and sport. Use the sample nutrition plans and case studies for various sports and situations to help facilitate the implementation of those recommendations. Get time-saving food prep and meal planning tips to help keep your unique nutrition plan on track. And if your goal is to gain muscle, lose fat, or recover from an injury, that's covered as well. If you want to train hard, perform to the best of your ability, recover quickly, and maintain a competitive edge over your opponent, let Nutrient Timing be your guide. It will give you insight into the ideal types of nutrients to consume, their quantities, and their timing to enhance your performance and achieve your goals.Earn continuing education credits/units! A continuing education exam that uses this book is also available. It may be purchased separately or as part of a package that includes both the book and exam"--
"The book explores how strategic timing of nutrients can optimize training, boost performance, and accelerate recovery. It uses scientific findings to create practical recommendations for all athletes. Topics include workout-based nutrition, weight loss or gain, special diets, and nutrition for muscle maintenance and growth"--
Not what, but when? Why nutrient timing matters -- Identify your timing needs -- Go harder for longer with carbohydrates -- Recover faster with protein -- Meet energy needs with fat -- Elevate performance with vitamins and minerals -- Sustain high performance with hydration -- Gain the edge with supplements -- Strategies for training and competition -- Endurance training and competition -- Strength, power, and team sport training and competition -- Special considerations -- Prep and plan ahead.
Includes bibliographical references and index.
Keywords: Athletes -- Nutrition